2008
DOI: 10.1002/jcu.20506
|View full text |Cite
|
Sign up to set email alerts
|

Combined local and systemic methotrexate treatment of viable ectopic pregnancy: Outcomes of 31 cases

Abstract: Combined MTX administration is effective and safe for treating viable cesarean scar pregnancies but is less successful for viable tubal or interstitial pregnancies. Reproductive outcomes following the combined MTX treatment are comparable to other treatment modalities for ectopic pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…12 000 IU/L in which systemic methotrexate might not be applicable. Therefore, to improve treatment outcomes some authors combined the use of both local and systemic methotrexate and reported high success rates [26,27]. Whether this combined modality is a better treatment option than single therapy is outside the scope of this review and remains to be studied.…”
Section: Cheung Ultrasound-guided Local Methotrexate Injection In Cspmentioning
confidence: 93%
“…12 000 IU/L in which systemic methotrexate might not be applicable. Therefore, to improve treatment outcomes some authors combined the use of both local and systemic methotrexate and reported high success rates [26,27]. Whether this combined modality is a better treatment option than single therapy is outside the scope of this review and remains to be studied.…”
Section: Cheung Ultrasound-guided Local Methotrexate Injection In Cspmentioning
confidence: 93%
“…Lai et al 21 (Table 2). Smorgick et al 23 evaluated combined local and systemic methotrexate treatment in 31 patients with a viable ectopic pregnancy, which was successful in all CSP cases (n 5 5). Although a 2 nd dose was required in 4 of 5 cases of CSP, surgical intervention could be avoided.…”
Section: Medical Treatmentmentioning
confidence: 98%
“…The authors concluded that although this method was safe for cesarean scar pregnancies, it was less successful for tubal and interstitial pregnancies. 18 Other treatment options reported include expectant management of a 6-week intramural pregnancy 2 and intrafetal potassium chloride injected transcervically with abdominal sonographic guidance.…”
mentioning
confidence: 99%
“…14,16 Although systemic methotrexate treatment and surgery are accepted modalities for tubal pregnancies, they are less effective for intramural pregnancies. 18 Sonographic-guided local methotrexate injections into gestational sacs of intramural pregnancies have been suggested. Smorgick et al evaluated the outcomes of combined local and systemic methotrexate treatment of unruptured viable ectopic pregnancies.…”
mentioning
confidence: 99%